DIGITAL MARKETING ANALYSIS OF TIKTOK AFFILIATE INCOME ON HP CASE PRODUCTS (CASE STUDY OF TIKTOK ACCOUNT @YULIFEB15) - Yulikhah Yulikhah; Fakhruddin Kurnia M (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the income of Tiktok Affiliate in the case study of the @yulifeb15 account. Tiktok Affiliate is one of the programs from Tiktok that allows Tiktok users to generate income through product promotions embedded in affiliate links. Tiktok Affiliate has recently inspired many people to sell and collaborate with sellers on Tiktok Shop by displaying interesting and quality content or videos, as an opportunity to earn rupiah, and provide opportunities for new Tiktok users to try to dive into the modern digital world today by developing communication and sharing information. This research was conducted through various approaches such as case studies, content analysis, in-depth interviews, and observations. The purpose of this study is to deeply understand the success of the Tiktok account @yulifeb15 as a Tiktok Affiliate in increasing income. And can understand effective marketing strategies in Tiktok Affiliate to measure the impact of digital marketing on the income of the Tiktok account @yulifeb15, through digital marketing techniques such as creating interesting content, interacting with the audience, and using the features available in the Tiktok Shop will influence purchasing interest and increase income.